Safe from cotton pests! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
'We appreciated reading the article on Safety is the hardest word' writes the Director of the Association of Planters and Growers of Togo (APE-TO) from Atakpamé in Togo. 'The next one, on hydroponics, was very interesting, but the one which really...